INUMERATION OF THE EFFECT OF TRADITIONAL MEDICINE ON DRY EYES (International Journal of Food and Nutritional Sciences, 2021)
According to ancient research methodology, before establishing any theory, the findings should be subjected through some sequential steps. The research work is done to draw some conclusions or the Nigamana from the findings and results. To correlate the findings with the results, discussion or the Upanaya is needed. Hence, this is the most important part of any research work. It comprises the discussion of important points from Conceptual Study as well as the results obtained from Clinical Study. It is the step which helps in understanding and interpreting the subject with reference to its merits and demerits, and guides to the conclusive judgment. In this aspect the, discussion becomes a necessary part of any research work. Chakshushya, the term indicating regeneration of eye sight was in practice in India since centuries. The classics of ancient Indian’s wisdom have invented and practiced many drugs like Triphala, Saptamrita lauha etc. diets, procedures i.e. Tarpana and regimen for the benefit of the eyes. Promotion of the visual acuity was considered as one of the priorities in the branch of Shalakya Tantra of Ayurveda. Tarpana karma has been indicated in several eye diseases by various Acharya’s but the main emphasis has been given on Dry eyes. Hence, here dry eyes selected for present study to assess the effect of ayurveda drug.